Avaliação de óleos lubrificantes aplicados em peças estampadas perante o tratamento de efluentes e qualidade de pintura - Ávila, Aline Oliveira de (2019)
The chemicals used to perform effluent treatment result in high costs for companies. Seeking to find alternatives to this problem, the present research evaluates impregnated stamping lubricants in the manufacturing stages prior to surface preparation, in order to select the stamping lubricant that facilitates effluent treatment. It is essential that, when selecting the lubricant that meets this requirement, the surface preparation and painting process is not affected For this reason, this research also evaluates the painting quality against its lubricant type In the present study, mineral, vegetable, vegetable oil ester and mineral oil with additives are evaluated In the laboratory analysis to evaluate the best condition for effluent treatment, the simulation of physicochemical treatment was carried out using the Jar test Milan® 1026 model equipment. The physicochemical simulation used degreasing and phosphating bath samples for comparison purposes in the research stages Thus, two types of bath were evaluated prepared bath and aged bath. The prepared bath was designed specifically for the experiments 2000 ml of water, 20 ml of ferritic phosphate and 60 ml of degreaser), while for the aged bath a project partner company's 5 month old manufacturing process tank was used. To perform the simulation of the physical and chemical treatment, 14 specimens were immersed in each type of lubricant under evaluation and then sprayed with each type of bath under study Therefore, it was possible to obtain the generation of liquid waste which was collected after the washing process of the specimens of each experimental condition, generating effluents that provided the subsequent experiments the possibility of characterization. The physicochemical analysis evaluated the influence of the lubricant type on the effluent treatment efficiency through the removal of Chemical Oxygen Demand (pH evaluation, electrical conductivity and oil charges present in the baths To analyze the best lubricant alternative when it comes to painting level, adhesion testing was performed after specimens were dipped into the stamping lubricants and then bathed with the prepared phosphating bath sample and subjected to the paint manufacturing process of the partner company. Taking into account effluent treatment efficiency and painting quality, the lubricant that meets this premise is of a vegetable character.